Analytical estimation of the values of the maximum side lobes of correlation functions of complex nonlinear discrete signals - Gorbenko, I.D.; Zamula, A.A. (Radiotekhnika, 2017)
The problems of synthesizing nonlinear discrete signal systems for their use in information and communication systems (ICS) as physical data carriers for solving the problems of information security and noise immunity of ICS in conditions of various kinds of influences on the part of the attacker are considered. A method for synthesizing derived signal systems based on nonlinear characteristic discrete signals is proposed. The results of the investigation of the properties of this class of signals are presented. It is shown that the use of such systems of nonlinear signals will improve the information security and noise immunity.